Exploration of Ethnomathematics of House and Traditional Music Tools Biak-Papua Cultural - Alvian M Sroyer; Jonner Nainggolan; Ida M Hutabarat (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
This research is an ethnomathematics study of the Biak Papuan community. The ethnomathematics studied are houses and traditional musical instruments. The shape and style of the traditional Biak house still remain to this day. The purpose of this study was to examine and reveal the relationship between mathematics and the traditional home culture of the Biak community, namely rum Som, rum Sram and Sram Mankubui and traditional musical instruments namely Tifa. The research method used is an exploratory survey method with a qualitative approach. The results showed that the shape of the roof of rum Som, rum Sram, Sram Mankubui was rectangular, half elliptical and triangular trapezoid. Whereas Tifa's musical instruments look like the two most belted cones combined.